Association between Physical Activity and the Incidence of Obesity in Adolescents - Aziz, Syaifallah (ProNers, 2023)
Background: The incidence of obesity among adolescents is rising annually. Obesity may also increase the risks of morbidity and mortality at an earlier age. It is due to the imbalance of energy that accumulates continuously. This imbalance of energy intake might be predisposed by an increased food intake and lack of physical activity. Aim: To investigate the association of physical activity with the incidence of obesity in adolescents. Method: This is a quantitative study with a cross-sectional design. The total sample was 245 high school students of SMAN 1 Singkawang, recruited through a consecutive sampling method. Data was collected including height and body weight to calculate the body mass index (BMI). The Physical Activity Questionnaire for Adolescents (PAQ-A) was used to screen the levels of physical activity. The Chi-Square test was used for the bivariate analysis. Results: Of 245 respondents, 69.8% and 30,3% were non-obese and obese, respectively and 58.5% regularly performed a light physical activity. The bivariate analysis shows there is no significant association between physical activity and the incidence of obesity among adolescents with p = 0.028. Conclusion: There was association the physical activity and the incidence of obesity among adolescents.Keywords: physical activity, obesity, adolescents